Prevalence of Candida albicans and non-albicans isolates from vaginal secretions: comparative evaluation of colonization, vaginal candidiasis and recurrent vaginal candidiasis in diabetic and non-diabetic women - Gunther,Luciene Setsuko Akimoto (2014)
CONTEXT AND OBJECTIVE: Vulvovaginal candidiasis (VVC) is caused by abnormal growth of yeast-like fungi on the female genital tract mucosa. Patients with diabetes mellitus (DM) are more susceptible to fungal infections, including those caused by species of Candida. The present study investigated the frequency of total isolation of vaginal Candida spp., and its different clinical profiles - colonization, VVC and recurrent VVC (RVVC) - in women with DM type 2, compared with non-diabetic women. The cure rate using fluconazole treatment was also evaluated. DESIGN AND SETTING: Cross-sectional study conducted in the public healthcare system of Maringá, Paraná, Brazil. METHODS: The study involved 717 women aged 17-74 years, of whom 48 (6.7%) had DM type 2 (mean age: 53.7 years), regardless of signs and symptoms of VVC. The yeasts were isolated and identified using classical phenotypic methods. RESULTS: In the non-diabetic group (controls), total vaginal yeast isolation occurred in 79 (11.8%) women, and in the diabetic group in 9 (18.8%) (P = 0.000). The diabetic group showed more symptomatic (VVC + RVVC = 66.66%) than colonized (33.33%) women, and showed significantly more colonization, VVC and RVVC than seen among the controls. The mean cure rate using fluconazole was 75.0% in the diabetic group and 86.7% in the control group (P = 0.51). CONCLUSION: We found that DM type 2 in Brazilian women was associated with yeast colonization, VVC and RVVC, and similar isolation rates for C. albicans and non-albicans species. Good cure rates were obtained using fluconazole in both groups.